The thermodynamics of partitioning of phenolic compounds between aqeous solution and model membrane systems - James, Michael John (1983)
The distribution behaviour of phenolic compounds between aqueous solution and the bulk organic solvents, n-octanol and cyclohexane, has been investigated over a range of temperature. The temperature dependence of partitioning of the phenolic compounds between aqueous solution and dimyristoyl phosphatidyl choline (DMPC) liposomes, below the phase transition temperature, has also been examined. From the experimental data, the thermodynamic parameters of free energy, enthalpy and entropy of transfer for the substituted phenols between aqueous solution and the three lipoidal environments have been derived. The non-covalent interactions and structural changes involved in the transfer of the phenolic solutes from aqueous solution to the various model membrane system could then be determined. Analysis of the thermodynamic data showed that the overall partitioning of phenolic solutes from aqueous solution to DMPC liposomes, below the phase transition temperature, was different than the transfer of the same solutes from aqueous solution to either n-octanol or cyclohexane. There were similarities between the three aqueous/model membrane systems however. The values of the partition coefficients in the aqueous/n-octanol system more closely resembled, in both absolute and relative terms, the values in the aqueous/ liposome system, than did the aqueous/cyclohexane partition coefficients. Solute-lipid, as well as solute-water interactions were found to be important for partitioning in both the aqueous/liposome and aqueous/n-octanol systems, whilst only solute-water interactions were significant for partitioningiin- the aqueous cyclohexane system. The transfer of phenols from aqueous solution to DMPC liposomes was entropy driven, whilst partitioning into n-octanol and cyclohexane was either enthalpy or entropy controlled depending on type of substituent on the molecule. Enthalpy-entropy compensation was found to be present for partitioning of phenols in the aqueous/liposome and aqueous/cyclohexane systems, but not in the aqueous/n-octanol system.